Revamping Parkinson’s disease therapy using PLGA-based drug delivery systems - Jude Majed Lababidi; Hassan Mohamed El-Said Azzazy (npj Parkinson's Disease)
Abstract Parkinson’s Disease (PD) involves degeneration of dopamine-producing neurons, mitochondrial dysfunction, alpha-synuclein aggregation, neuroinflammation, and gut-brain axis disturbances. Despite the availability of pharmacological treatments, these interventions fail to prevent disease progression due to their limited ability to penetrate the blood-brain barrier (BBB) and systemic side effects. Phytochemicals, known for their antioxidant and neuroprotective properties, offer a complementary approach to PD treatment. However, their therapeutic potential is limited by rapid metabolism and poor bioavailability. Several nanoparticles were suggested to enhance the stability and bioavailability of therapeutic agents while enabling controlled release and improved BBB penetration. This review is focused on the use of poly (lactic-co-glycolic acid) (PLGA)-based nanosystem as advanced drug delivery carriers for PD due to its versatility, safety, biodegradability, and extensive studies which evaluated the use of PLGA for drug delivery. It also evaluates their use for encapsulating pharmacological drugs such as dopamine agonists, dopamine precursors, COMT inhibitors, and MAO-B inhibitors, addressing the limitations of conventional therapies. Additionally, the review highlights the utility of PLGA nanoparticles in delivering phytochemicals with neuroprotective effects such as polyphenols, flavonoids, and coumarins to overcome challenges associated with their solubility and stability and ultimately enhance their activities for managing PD.